Computational studies on horseshoe shape pocket of human orexin receptor type 2 and boat conformation of suvorexant by molecular dynamics simulations. (8th March 2018) - Bai, Qifeng; Pérez‐Sánchez, Horacio; Shi, Zhuoyu; Li, Lanlan; Shi, Danfeng; Liu, Huanxiang; Yao, Xiaojun
Abstract : The FDA approved drug suvorexant binds to the horseshoe shape pocket of OX2 R with the boat conformation. The horseshoe shape pocket plays an important role on the biological activity of OX2 R in the cell membrane. To study the binding mechanism between the horseshoe shape pocket of OX2 R and boat conformation of suvorexant, the crystal structures of wild type and N324A mutant of OX2 R in complex with antagonist suvorexant are chosen to perform molecular dynamics (MD) simulations, QM/MM, and MMGBSA calculations. By comparison with the wild type of OX2 R, the results show the 1, 2, 3‐triazole and p ‐toluamide groups of suvorexant are changed in the N324A mutant of OX2 R during 200 ns MD simulations. The QM/MM and weak interaction analysis are employed to calculate the non‐covalent bonds interaction between suvorexant and key residues in the wild type and N324A mutant of OX2 R. The MMGBSA calculations indicate the entropy energy is an important influence factor for suvorexant affinity in the distorted horseshoe shape pocket of OX2 R. Our results not only show the horseshoe shape pocket of OX2 R is the necessary conformation for the binding of antagonist suvorexant, but also give the important sites and structural features for antagonist design of OX2 R. Abstract : Binding mechanism between boat conformation of suvorexant and horseshoe shape pocket of OX2 R is studied. The results show the change mechanism of boat conformational suvorexant in the horseshoe shape pocket of OX2 R. It supplies the structural feature information for further drug design of OX2 R.